Increasing access to smoking cessation treatment among Latino smokers using case management. (September 2019) - Cartujano-Barrera, Francisco; Perales, Jaime; Arana, Evelyn; Cox, Lisa Sanderson; Yeh, Hung-Wen; Ellerbeck, Edward F.; Richter, Kimber P.; Cupertino, Ana Paula
Abstract: Introduction: Disparities exist among Latino smokers with respect to knowledge and access to smoking cessation resources. This study tested the feasibility of using case management (CM) to increase access to pharmacotherapy and quitlines among Latino smokers. Methods: Latino smokers were randomized to CM ( n = 40) or standard care (SC, n = 40). All participants received educational materials describing how to utilize pharmacy assistance for cessation pharmacotherapy and connect with quitlines. CM participants received four phone calls from staff to encourage pharmacotherapy and quitline use. At 6-months follow-up, we assessed the utilization of pharmacotherapy and quitline. Additional outcomes included self-reported smoking status and approval for pharmacotherapy assistance. Results: Using intention-to-treat analysis, CM produced higher utilization than SC of both pharmacotherapy (15.0% versus 2.5%; P = 0.108) and quitlines (12.5% versus 5.0%; P = 0.432), although differences were not statistically significant. Approval for pharmacotherapy assistance programs (20.0% versus 0.0%; P = 0.0005) was significantly higher for CM than SC participants. Self-reported point-prevalence smoking abstinence at 6-months were 20.0% and 17.5% for CM and SC, respectively ( P = 0.775). Conclusions: CM holds promise as an effective intervention to connect Latino smokers to evidence-based cessation treatment.